(untitled) (Western European Journal of Historical Events and Social Science, 2024)
This article explores the psychological interpretation of the influence of emotions on personal activity from the perspective of Eastern thinkers. Drawing from various Eastern philosophies and traditions, it examines the ways in which emotions are understood, experienced, and navigated within the context of personal growth and well-being. The article highlights key themes such as the wisdom of emotions, their transformative potential, the role of mindfulness, the integration of opposites, the recognition of interdependence, and the transcendence of egoic patterns. It also touches upon practices like meditation, selfcompassion, and non-identification with emotions. By gaining insights into the Eastern perspectives on emotions, individuals can enhance their emotional intelligence and cultivate a more balanced and fulfilling approach to their emotional lives